Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran - Mehrabian, Fatemeh; Azizi, Kourosh; Bazgir, Eadi; Darvishnia, Mostafa (Zootaxa, 2017)
Discotylenchus lorestanensis sp. n., recovered from soil near Persian oak (Quercus brantii Lindl.) from the Lorestan province of Iran, is described and illustrated based on morphological and molecular characters. The new species is characterized by females with a body length of 449–566 μm, a = 28.3–39.5) b = 5.2–5.8, c = 6.2–8.1, c’ = 5.8–9.2, V = 63.3–71.1%, stylet 8–9 μm, spermatheca lobed and offset, filled with rounded sperm, post-vulval uterine sac (PUS) 4.8–6.5 μm, tail length 66–78 μm, not filiform, tapering to a rounded tip; and males with spicules 13–16 μm long. The new species has unique molecular sequences of SSU and the D2–D3 region of LSU expansion segments, Discotylenchus lorestanensis sp. n., separated from all known species of the Tylenchidae. We also provide an updated dichotomous key to the genus Discotylenchus.